The Mediating Role of Self-Compassion in the Relationship Between Perfectionism and Subjective Well-Being - Sussan Rahimzade; Atosa Mirzasadeghi (پژوهشنامه روانشناسی مثبت, 2023)
With the introduction of positive psychology, the attention of psychology has shifted from focusing on disorders and psychological problems to the scientific study of positive personal experiences traits and the institutions that evolve these experiences. This study aimed to investigate the mediating role of self-compassion in the relationship between perfectionism and subjective well-being (i.e., life satisfaction positive and negative affect). The research design was descriptive-correlational and the sample included 353 students (233 females and 120 males) at Islamic Azad University- South Tehran Branch, Iran. The participants responded to Self-Compassion Scale Short Form (SCS-SF), Life Satisfaction with Life Scale (SWLS), Positive and Negative Affect Schedule (PANAS) and Tehran Multidimensional Perfectionism Scale (TMPS). The results of path analysis showed that perfectionism and self-compassion explained 33% of the variance of life satisfaction, 15% of the variance of positive affect, and 22% of the variance of negative affect. Furthermore, 17% of the variance of self-compassion was explained by perfectionism. Thus, the research has some implications for overcoming the destructive effects of perfectionism on subjective well-being through teaching self-compassion.IntroductionPositive psychology is the scientific study of what makes life most worth living, focusing on both individual and societal well-being (Csikszentmihalyi & Seligman, 2000). Subjective well-being is one of the key topics in positive psychology, which has received increasing attention from researchers, politicians, media, and people. It is one of the significant and influential variables in mental health and refers to a feeling of happiness and life satisfaction (Diener, 2021). Subjective well-being (SWB) is the scientific term for happiness and life satisfaction—thinking and feeling that your life is going well (Pavot & Diener, 1993). Research findings indicate that personality is one of the most powerful and stable variables in determining subjective well-being (Steel et al., 2008) and perfectionism is a personality trait can play a vital role in subjective well-being.Perfectionism is a personality characteristic as striving for being flawless and setting exceedingly high standards for performance accompanied by tendencies for overly critical self-evaluations and concerns about negative evaluations by others (Flett & Hewitt, 2002; Frost & Marten, 1990). One of the most widely-researched multidimensional models of perfectionism is Hewitt and Flett's (1991) model, which describes self-oriented, other-oriented, and socially prescribed perfectionism.One of the variables that plays a significant role as a mediator in many cases and increases a person's ability to cope with failures and deprivations is self-compassion (Sbarra et al., 2012). Self-compassion is a coping strategy that helps individuals face their fate and the consequence of their deeds (Gerber & Anaki, 2021). It involves three basic components: self-kindness vs self-judgment, a sense of common humanity vs isolation, and mindfulness vs over-identification. These components combine to create a self-compassionate frame of mind (Neff, 2003). The purpose of this study was to know more about the dimensions of perfectionism, the components of subjective well-being and self-compassion, and also to present a model that could account for the relationship between perfectionism and subjective well-being with the mediating role of self-compassion. MethodThe research design of the present study was descriptive-correlational. The criteria for entering the study were the desire to participate in the research and being a student at Islamic Azad University, Southern Tehran Branch in 2021-2022. Due to the online nature of the instruction during the Covid-19 pandemic, the addresses of the online courses and groups were received from the university website. Then. with the permission of the professors, the questionnaires were sent by WhatsApp and Telegram social networks. There was no time limit and obligation for completing the questionnaires. A sample of 353 (233 females and 120 males) students responded to the Self-Compassion Scale Short Form (SCS-SF), Life Satisfaction with Life Scale (SWLS), Positive and Negative Affect Schedule (PANAS) and Tehran Multidimensional Perfectionism Scale (TMPS). The data were analyzed by using Pearson's correlation coefficient, path analysis method, and bootstrap methods.                                            To test the hypotheses of the study, path analysis using the bootstrap method was used. the unstandardized and determined estimation of the paths of the model are presented in Table 2 is reflected.                                                                                                       Table 2: Summary of Path Analysis Results Based on Bootstrap Methohypotheses (paths)EstimateS.E.C.R.StandardizedEstimateSelf-oriented perfectionism→Self-compassion-.314.058-5.392**-.31Other-oriented perfectionism→Self-compassion-.060.063-.964-.06Socially prescribed Perfectionism→Self-compassion-.217.046-4.751**-.26Self-oriented perfectionism→Satisfaction with life-.093.059-1.581-.09Self-oriented perfectionism→Positive affect.080.0711.124 .07Self-oriented perfectionism→Negative affect.058.067.865.05Other-oriented perfectionism→Satisfaction with life.072.0611.171 .07Other-oriented perfectionism→Positive affect.121.0741.635 .10Other-oriented perfectionism→Negative affect-.013.069-.182 .01Socially prescribed Perfectionism→Satisfaction with life-.095.046-2.082-.11Socially prescribed Perfectionism→Positive affect-.063.055-1.138-.06Socially prescribed Perfectionism→Negative affect.289.0525.579** .28Self-compassion→Satisfaction with life.388.0527.465** .39Self-compassion→Positive affect.442.0637.035** .38Self-compassion→Negative affect-.507.059-8.655**-.42P*<0/05    P**<0/001   The results of path analysis showed that perfectionism and self-compassion accounted for 33% of the variance of life satisfaction, 15% of the variance of positive affect, and 22% of the variance of negative affect. Moreover, 17% of the variance of self-compassion was explained by perfectionism ConclusionThe present study aimed to present a model of the relationship between perfectionism and subjective well-being via the mediation of self-compassion. The results showed that self-compassion had a positive relationship with life satisfaction and positive affect. Also, there was a negative negative relationship between self-compassion and negative affect, which is consistent with the definition of subjective well-being and in line with previous research in the field (Bluth & Neff, 2018; Gilbert & Procter, 2006). To explain this finding, it should be considered that painful experiences, suffering, and failure are inevitable throughout life. Self-compassionate people accept themselves as they are and treat themselves kindly and without judgment. As a result of this, when self-compassion increases, subjective well-being increases as well (Neff & Costigan, 2014; Stoeber et al., 2020).Furthermore, the results showed that self-oriented and socially prescribed Perfectionism had a negative relationship with self-compassion, and other-oriented perfectionism did not have a significant relationship, which is similar to the research results (Stoeber et al., 2020). Stoeber (2014) distinguished other-oriented perfectionism from self-oriented and socially prescribed Perfectionism. The findings of the research indicated that with the increase in perfectionism, students' self-compassion decreases, and with the decrease of self-compassion, subjective well-being decreases. Perfectionism by reducing self-compassion leads to a decrease in subjective well-being. This shows that self-compassion is one of the structures by which the dimensions of perfectionism exert their negative effects on the subjective well-being components. Perfectionists who experience less self-compassion show higher levels of negative affect and lower levels of life satisfaction and positive affect. It seems that a high level of self-compassion creates a caring force that reduces the negative effects of perfectionism on subjective well-being (Bluth & Neff, 2018; Neff, 2021).This study has some limitations. First, it was conducted among the students of the IAU-South Tehran Branch, therefore, the results are limited to this specific sample. In addition, this research was conducted during the covid-19 pandemic, which had an impact on subjective well-being, and the results may be affected by the time situation resulting from the pandemic. It is also suggested that other variables of personality, age, gender, and marriage should be investigated to present a better picture of the variables involved in the study. Because self-compassion can be taught with the help of targeted interventions, it is suggested that self-compassion training be involved in the educational programs of schools, universities. This can be done and by preparing brochures, training in mental health clinics and using media to pay attention to training parents to raise self-compassionate children. Ethical Consideration Compliance with Ethical Guidelines: Participation was voluntary. The participants were informed that they could withdraw from the study at any time. All ethical issues like informed consent and confidentiality of participants’ identifications were compiled based on ethical committee of Islamic Azad University- South Tehran Branch.Authors’ Contributions: All authors contributed to the study. First author contributed to the conception and design of the study, as well as the acquisition, analysis and interpretation of data, drafting the article, andwriting the entire manuscript. Second author contributed to developing the study design and to final approval of the version to be submitted. Both authors contributed to the article and approved the submitted version.   Conflict of Interest: The authors declare no conflict of interest for this study.Funding: This study was conducted with no financial support.Acknowledgment: The authors thank all participants in the study.    *. Corresponding author